SAFETY ATTITUDES AS ASSESSED BY NURSES IN A TERTIARY HOSPITAL IN THE PHILIPPINES - C. Barcelona, Airene Arcemaice; A. Lazaro , Ferdinand; de Leon, Kathleen G.; Santos , Ornest S.; Aviguetero , Adelson V.; Lita , Kennedy; Martinez , Cecilia O. (LIFE: International Journal of Health and Life-Sciences, 2024)
This study was conducted to assess safety attitudes in the clinical area of a tertiary hospital in the Philippines. Respondents of the study were nurses purposively selected as they satisfied the criteria set by the researchers as follows: they have worked at the hospital for more than 1 year and are willing and able to participate in the conduct of this study. Results showed that most of the nurse respondents belonged to the 31 – 40-year-old; females; assigned to the Adult Female Ward; Nurse 1; working for 1 – 3 years in the current unit/area of assignment; had been working at the current hospital/workplace for 1 – 3 years; and with 30 to 40 working hours per week; high nurse’s perceived degree of safety attitude in the clinical area in terms of teamwork culture, safety climate, job satisfaction, stress recognition, perception of management on a unit level, perception of management on a hospital level, and working conditions; there were no significant differences in the nurse’s perceived degree of safety attitude in the clinical area in terms of the dimensions: Teamwork Climate, Safety Climate, Job Satisfaction, Stress Recognition, Management on a Hospital Level, and Work Condition when grouped according to age; in terms of all the dimensions: Teamwork Climate, Safety Climate, Job Satisfaction, Stress Recognition, Management on a unit level, Management on a Hospital Level, and Work Condition when grouped according to gender; in terms of the dimensions: Teamwork, Job Satisfaction, Management on a Unit Level, Management on a Hospital Level, and Work Condition when grouped according to the unit of assignment; in terms of all the dimensions: Teamwork Climate, Safety Climate, Job Satisfaction, Stress Recognition, Management on a unit level, Management on a Hospital Level, and Work Condition when grouped according to work position; in terms of the dimensions: Safety Climate, Job Satisfaction, Stress Recognition, Management on a Unit Level, Management on a Hospital Level, and Work Condition when grouped according to the length of time working in the current unit of assignment; in terms of the dimensions: Teamwork Climate, Safety Climate, Job Satisfaction, Stress Recognition, Management on a Hospital Level, Management on a Hospital Level, and Work Condition when grouped according to the Length of Time Working in San Lazaro Hospital; in terms of the dimensions: Safety Climate, Stress Recognition, Management on a Hospital Level, and Work Condition when grouped according to Work Hours per Week; and Hypothesis 1 is rejected at point where there is/are significant difference/s: in the dimension Management on a Unit when grouped according to age; in the dimensions Safety Climate, and Stress Recognition when grouped according to the unit of assignment; in the dimension Teamwork Climate when grouped according to the length of time working in the current unit of assignment; in the dimensions: Teamwork Climate, Job Satisfaction, and Management on a Unit Level when grouped according to Work Hours per Week. It was recommended that nurses should maintain their safety attitudes in nursing units and across hospitals to have a very positive outcome of patient safety and that they participate in the conduct of the Staff Development Programs developed through the results of this study; patients to have confidence in the services being rendered to them by the nurses; nursing leaders/managers to adequately assess the safety culture in their workplace and clearly articulate a framework to guide their staff nurses as they work to increase safety within their work settings; they must contribute to the development of plans, future training, and programs that will enhance the safety culture and level of commitment of staff nurses and the nursing service as a whole; the hospital to implement the Staff Development Program developed through the results of this study, that they should also identify the strengths and areas for improvement in the clinical area to develop appropriate interventions to maintain safety inside the hospitals; the Department of Health to use the results of this study as a basis for planning for realistic health programs and projects that will genuinely address the safety of nurses and patients in the clinical areas; they can also use the results of this study as part of their policy reforms that can contribute to nurses’ and patient safety culture; and future researchers to use this study as a reference for their future research endeavors.